Spatial Durbin Model on the Utilization of Delivery at Health Facilities: A 2017 Indonesian Demographic and Health Survey Analysis - Wahyuni, Indah Sri; Gustina, Ira; Makful, Martya Rahmaniati; Eryando, Tris (Kesmas, 2024)
The utilization of delivery at health facilities is a major intervention in reducing 16 to 33% of deaths. This study aimed to determine the model of utilization of delivery at health facilities in Indonesia in 2017 and its influential factors. This study used secondary data from the 2017 Indonesian Demographic and Health Survey using a Spatial Durbin Model (SDM) approach. The population was mothers aged 15 – 49 years, spread across 34 provinces of Indonesia, and had 15,321 samples. The results showed that the Moran’s I value was positive (0.146) and significant at p-value = 0.007, indicating clustered regions with similar characteristics. The SDM modeling estimation results (R2 = 91.61%) presented those dependent and independent variables that influenced the utilization of delivery at health facilities and its influential factors. The significant and most dominant direct factor that influenced the utilization of delivery at health facilities was pregnancy visits, while the most dominant indirect factor was socioeconomic status. Therefore, further policy planning is expected to be based on regional specificities, and effective intervention programs should be designed based on these factors.